“Towards Stadium Attendance: Evaluating Market Values of Ghanaian Football Clubs as a Driver for Sponsorship” - Frank Appiah Kusi; Stanley Anyang Kaakyire; Evelyn Kessewaah; Annie Yayra Hiamey (The Bioscan, 2026)
Drawing on the Sport Value Framework, Resource-Based View, and Stakeholder Theory, this study investigates the relationship between sponsorship and market value in the Ghana Premier League (GPL), focusing on how club and player valuations influence stadium attendance and financial sustainability. Using a quantitative design, data were collected from 628 fans through online surveys distributed via Facebook, Telegram, and WhatsApp.